Industrialization and development in the third world - Chandra, Rajesh (London, 1992)
Developing countries have undergone significant industrialization in the last three decades. Yet industrial growth reveals marked spatial inequalities in terms of both country and location. The Newly Industrialised Countries have achieved spectacular growth in sharp contrast to many other countries of the South. Industrial structure has changed, moving away from labour intensive industries to more technologically advanced manufacturing. Developing countries have had considerable success in penetrating developed country markets but they are now encountering more market restrictions. The role of the government in the development of the economy is also changing. Increasingly, countries are turning towards export-orientated industrialization strategies and privatization whilst their governments are emphasising their facilitative role.
Keywords: Developing countries industries